Causal relationship between gut microbiota and male erectile dysfunction: a Mendelian randomization analysis - Chen, Shuaiqi; Liu, Xiaolong; Wu, Shangrong; Sun, Guangyu; Liu, Ranlu (Frontiers in Microbiology, 2024)
Several observational studies have reported an association between gut microbiota and male erectile dysfunction (ED). However, it remains unclear whether there is a causal relationship between gut microbiota and male ED. Thus, we aimed to investigate the potential causal relationship between gut microbiota and male ED through Mendelian randomization (MR) analysis.To assess the causal relationship between gut microbiota and male ED, we performed a two-sample MR analysis.We obtained gut microbiota genome-wide association studies (GWAS) data from the MiBioGen consortium and publicly available GWAS data on male ED from the OPEN GWAS database. Subsequently, we performed a two-sample MR analysis to evaluate the causal relationship between gut